2009
DOI: 10.1002/cne.22099
|View full text |Cite
|
Sign up to set email alerts
|

Peptidergic clock neurons in Drosophila: Ion transport peptide and short neuropeptide F in subsets of dorsal and ventral lateral neurons

Abstract: About 150 clock neurons are clustered in different groups in the brain of Drosophila. Among these clock neurons, some pigment-dispersing factor (PDF)-positive and PDF-negative lateral neurons (LNs) are principal oscillators responsible for bouts of activity in the morning and evening, respectively. The full complement of neurotransmitters in these morning and evening oscillators is not known. By using a screen for candidate neuromediators in clock neurons, we discovered ion transport peptide (ITP) and short ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
215
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 196 publications
(228 citation statements)
references
References 125 publications
10
215
1
2
Order By: Relevance
“…For example, sNPF mRNA is substantially more abundant in s-LNvs than in l-LNvs without being enriched ( Fig. 2A), consistent with recent immunohistochemical data (29). The transcription factor Dimmed and the octopamine receptor Oamb are only marginally enriched in l-LNvs but have very low expression in s-LNvs.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…For example, sNPF mRNA is substantially more abundant in s-LNvs than in l-LNvs without being enriched ( Fig. 2A), consistent with recent immunohistochemical data (29). The transcription factor Dimmed and the octopamine receptor Oamb are only marginally enriched in l-LNvs but have very low expression in s-LNvs.…”
Section: Discussionsupporting
confidence: 89%
“…1 on the s/l ranking. Consistent with these data, sNPF has very recently been shown by immunohistochemistry to be present in s-LNvs but not in l-LNvs (29). The lack of strong enrichment is almost certainly because there are many other neurons that express sNPF and/or because these other neurons have much higher sNPF mRNA levels than s-LNvs.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Interestingly, NPF was also found to be expressed in three of the LN d clock neurons in male flies (Lee et al, 2006). One of these NPF-positive LN d s is also CRY-positive and might be the so-called ''extra LN d ,'' that was shown to be an important E component (Rieger et al, 2006(Rieger et al, , 2009Johard et al, 2009). Lee et al (2006) reported that the expression of uas-reaper with an npfGal4 line leads to the ablation of all NPF neurons, including the three LN d s. In another recent study by Hamasaka et al (2010) the same npfGal4 line was used to ablate the NPF neurons with uas-hid.…”
mentioning
confidence: 95%
“…The short-NPF (sNPF) neuropeptide is expressed in the two LNds lacking NPF, as well as in the s-LNvs (Fig. 1D) (Johard et al 2009;Kula-Eversole et al 2010). Although similar in name, the sNPF and NPF neurotransmitters are very different in amino acid sequence and are encoded by different genes.…”
Section: Coordination Between Differentially Regulated Circadian Clocksmentioning
confidence: 99%